Compromised steady‐state germinal center activity with age in nonhuman primates. Issue 2 (15th December 2019) - Shankwitz, Kimberly; Pallikkuth, Suresh; Sirupangi, Tirupataiah; Kirk Kvistad, Daniel; Russel, Kyle Blaine; Pahwa, Rajendra; Gama, Lucio; Koup, Richard A.; Pan, Li; Villinger, Francois; Pahwa, Savita; Petrovas, Constantinos
Abstract: Age‐related reductions in vaccine‐induced B cells in aging indicate that germinal centers (GCs), the anatomical site where the development of humoral responses takes place, may lose efficacy with age. We have investigated the baseline follicular and GC composition in nonhuman primates (NHPs) with respect to their age. There was a marked reduction in follicular area in old animals. We found significantly lower normalized numbers of follicular PD1 hi CD4 T (Tfh) and proliferating (Ki67 hi ) GC B cells with aging, a profile associated with significantly higher numbers of potential follicular suppressor FoxP3 hi Lag3 hi CD4 T cells. Furthermore, a positive correlation was found between Tfh and follicular CD8 T cells (fCD8) only in young animals. Despite the increased levels of circulating preinflammatory factors in aging, young animals had higher numbers of monocytes and granulocytes in the follicles, a profile negatively associated with numbers of Tfh cells. Multiple regression analysis showed an altered association between GC B cells and other GC immune cell populations in old animals suggesting a differential mechanistic regulation of GC activity in aging. Our data demonstrate defective baseline GC composition in old NHPs and provide an immunological base for further understanding the adaptive humoral responses with respect to aging. Abstract : Steady‐state germinal center immune reactivity is compromised in aged NHPs. This loss of reactivity is characterized by changes in many GC associated cell populations including Tfh, B cells, and follicular Tregs.